From Fine Arts to Art History: Art History as a study Program at the University of Jaffna - Kirubalini, S.; Thivani, K.; Sanathanan, T. (University of Jaffna, 2022)
The discipline of art history rests on a visual-based knowledge that takes the visual as its object and method of inquiry. It investigates how art constitutes a transcendent and continuous expression of human content. Art history examines the history of the production, experience and consumption of visual arts. This research attempts to read the changes that occurred during the past four decades in the curriculum of the art history study programme known as Fine Arts until 2019 in the Department of Fine Arts at the University of Jaffna, in association with the changes in the local cultural landscape and the curriculums of similar study programmes at universities abroad. Since the area of study, theoretical frameworks, approaches, research methods, and methodologies of the Art History discipline were introduced to South Asia through colonialism, this paper examines the challenges, responses, adaptations, and changes that the discipline has undergone at the University of Jaffna. This social history reading is based on the archive in the Department of Fine Arts, newspaper clippings, curriculum, catalogues, and publications of the University Grant Commission, curriculum evaluation reports, and interviews.
Keywords: Art History; Curriculum; Fine Arts; Change; Cultural politics; Ideology